2017
DOI: 10.1177/2325967117741276
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Sports Medicine Fellowship Interviews: Structure and Organization of the Interview Day

Abstract: Background:Over the past few decades, there has been a trend toward an increasing subspecialization in orthopaedic surgery, with orthopaedic sports medicine being one of the most competitive subspecialties. Information regarding the application and interview process for sports medicine fellowships is currently lacking.Purpose:To survey orthopaedic sports medicine fellowship program directors (PDs) to better define the structure of the sports medicine fellowship interview and to highlight important factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…1,2 Recent studies have demonstrated that roughly 90% of orthopaedic surgery residents plan to pursue additional training after graduation for various reasons, including surgical skill development, employment opportunities/marketability, and perceived impact of fellowship training on clinical decision-making. [3][4][5] Despite the high number of orthopaedic sports medicine fellowship applicants, there is a paucity of information regarding the factors that applicants deem most important when applying. In 2015, Niesen et al 6 quantified the factors considered most and least important by residents applying to orthopaedic fellowships in all 9 subspecialties.…”
mentioning
confidence: 99%
“…1,2 Recent studies have demonstrated that roughly 90% of orthopaedic surgery residents plan to pursue additional training after graduation for various reasons, including surgical skill development, employment opportunities/marketability, and perceived impact of fellowship training on clinical decision-making. [3][4][5] Despite the high number of orthopaedic sports medicine fellowship applicants, there is a paucity of information regarding the factors that applicants deem most important when applying. In 2015, Niesen et al 6 quantified the factors considered most and least important by residents applying to orthopaedic fellowships in all 9 subspecialties.…”
mentioning
confidence: 99%
“…Yayac et al 5 found that most fellowship program websites are difficult to access and provide insufficient information for applicants on the selection process. A previous study by Haislup et al 6 similarly noted that little information could be found on program websites regarding interview day structure, program expectations of fellows, and the selection committee's desired applicant qualities. The SF Match website only provides generalized guidelines regarding standards of professionalism during the interview cycle.…”
mentioning
confidence: 99%
“…[13][14][15] Given the highly competitive nature of applying for orthopaedic sports medicine fellowships, it is imperative for applicants to have a sound understanding of the traditional interview structure and the most critical selection criteria for matching to an orthopaedic sports medicine fellowship program. In a 2017 study, Haislup et al 16 surveyed 38 fellowship PDs and provided useful information regarding the organization of orthopaedic sports medicine fellowship interviews prior to the COVID-19 pandemic. Within the pool of PDs surveyed, 42.1% stated that they interviewed 21 to 30 applicants per year and 28.9% have only 1 fellow per year at their respective program.…”
Section: Traditional Sports Medicine Fellowship Interview Processmentioning
confidence: 99%